Household Income Generation Strategies - Covarrubias, Katia (World Bank, Washington, DC, 2013)
This document presents results of a descriptive analysis of income-generating activities of 19 countries based on the Rural Income Generating Activities (RIGA) database. The RIGA database uses the rural sample of these countries’ nationally representative living standards surveys, while the present study pools rural and urban households to illustrate the characteristics and dynamics of household income generating strategies at the national level. Total household income is measured following the RIGA project methodology, which constructs net annual aggregates of income following a standardized approach. Income is disaggregated intomain categories which include agricultural wages, non-agricultural wages, crop activities, livestock activities, self-employment (household nonfarm enterprises), transfers, and other non-labor sources. Overall, all countries tend to have high levels of participation in on-farm activities regardless of the GDP per capita level, though there is a slight negative trend with increasing per capita GDP (PCGDP). Involvement in nonfarm activities rises with increasing PCGDP, with wealthier countries demonstrating higher levels of participation in the nonfarm sector than poorer countries.